Kuat Tekan Dan Porositas Beton Pofa Dengan Penambahan Silika Fume Di Air Gambut - Asmanovita, Ririn; Utama, Panca Setia; Olivia, Monita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
This study examined the compressive strength and porosity of PCC concrete and POFA concrete with the addition of silica fume soaked in peat water. POFA is used as a cement substitute with variations of 0% and 20% and the addition of silica fume is 10%. The design compressive strength is 20 MPa. Treatment of the specimens was carried out in normal water for 28 days and then immersed in peat water for 0, 7 and 28 days. The results of testing the compressive strength of concrete at 28 days of immersion in peat have increased 16.73% with 29.24 MPa in PCC concrete, 29.49% with 32.69 MPa in POFA 0% concrete and 17.58% with 25.77 MPa in POFA 20% concrete. The porosity value of PCC concrete at 28 days of peat decreased by 6.55%. A decrease in porosity values also occurred in POFA 0% concrete and POFA 20% concrete by 20% and 26.78% at 28 days of peat. Based on the test results, it can be concluded that replacing cement with POFA and adding silica fume to concrete has a positive impact on the compressive strength and porosity of concrete in peat water. Key words: Compressive strength, porosity, POFA, silica fume, peat water